ANALISIS KOMPARATIF KADAR ION MAGNESIUM EKSTRAK ETANOL BUAH JAMBU BIJI (Psidium Guajava L.) DENGAN VARIASI METODE EKSTRAKSI - Devina Ingrid Anggraini (Jurnal Farmasi Medica/Pharmacy Medical Journal (PMJ), 2026)
Red guava fruit (Psidium guajava L.) is rich in minerals, one of which is magnesium, which has the potential as a natural active ingredient in cosmetic formulations. To ensure the effectiveness and stability of this compound, a study of various extraction methods is needed to determine the most optimal technique in producing the highest magnesium ion levels. This study aims to compare the magnesium ion levels in 70% ethanol extracts of red guava fruit extracted using maceration and ultrasonic methods. An experimental approach was used to determine which method is more effective in producing optimal magnesium levels. Identification of magnesium ions was carried out qualitatively using the titan yellow test and the NaOH test. Quantitatively, the determination of magnesium ion levels was analyzed using UV-Vis spectrophotometry at a wavelength of 527.5 nm with the EBT color complex. To evaluate the effectiveness of the extraction method, a t-test was conducted on the magnesium content data to prove the significant effect of the different extraction techniques used. The results showed that both extracts contained magnesium ions. Analysis of magnesium ion levels in the ultrasonic method (260.47 mg/100 g) was proven to be higher than that in the maceration method (199.46 mg/100 g). The independent t-statistical test strengthens the research results by showing a significant difference between the two extraction methods (sig 0.000), so that ultrasonic is considered more effective in producing higher levels of magnesium ions. Keywords: ethanol extract, magnesium ions, red guava, UV–Vis spectrophotometry